Evaluation of Serial Casting for Boys with Duchenne Muscular Dystrophy: A Case Report. (1st January 2018) - Carroll, Kate; de Valle, Katy; Kornberg, Andrew; Ryan, Monique; Kennedy, Rachel
ABSTRACT: Aim : To report the effects of below-knee serial casting in two boys with Duchenne muscular dystrophy who presented with well-preserved strength and calf shortening. Methods : Bilateral below-knee serial casts were applied over two weeks with follow-up of daily stretching and wearing of customized night splints. Outcome measures were performed at baseline, 1, 3, 6, and 12 months post-casting. These included measures of calf length, leg strength, motor function, endurance, and spatio-temporal gait parameters. Results : Both boys completed serial casting with gains in muscle length. No adverse effects on strength or motor function were observed over a 12-month follow-up period.